Improving Students' IPS Learning Outcomes through TTS Media in Class IX.1 SMPN 25 Sijunjung - Busma Darmi (Formosa Journal of Multidisciplinary Research, 2022)
Learning media needs to be used to increase student’s interest and motivation in order to achieved learning objective.Crossword puzzle is one of the media that can be used to increase student’s interest and motivation. This research was conducted in class IX.1 SMPN 25 Sijunjun. The purpose of the research is to find out the improvement of student learning outcomes after applying the crossword puzzle methode in Social study learning at class IX.1 SMPN 25 Sijunjung with a total of 24 students.The data analysis technique used is qualitative data analysis technique which consists of data reduction, presentation data, and conclusion drawing. In the first cycle, the average percentage of student learning outcomes that reached the KKM was 73%. In the second cycle was 95% or it increase about 22%.